Stock assessment using spawning potential ratio in data poor fisheries for mahseer Tor tambroides (Bleeker, 1854) in Aceh Province, Indonesia - TEUKU FADLON HASER; MUH. SALEH NURDIN; EDDY SUPRIYONO; TRI HERU PRIHADI; SURI PURNAMA FEBRI; ANDRI YUSMAN PERSADA; TEUKU HADI WIBOWO; HERLINA PUTRI ENDAH SARI; KARTIKA APRILIA PUTRI; ANTONI ANTONI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Haser TF, Nurdin MS, Supriyono E, Prihadi TH, Febri SP, Persada AY, Wibowo TH, Sari HPE, Putri KA, Antoni. 2023. Stock assessment using spawning potential ratio in data poor fisheries for mahseer Tor tambroides (Bleeker, 1854) in Aceh Province. Biodiversitas 24: 6039-6047. Overexploitation of mahseer has led to a decline in population, posing a threat to its sustainability in the wild. Therefore, this study aimed to compare the length-based spawning potential ratio of the fish from Atu Suasah and Lawe Melang Rivers in Aceh Province. The experiment was conducted from January to August 2023, and the population dynamics parameters were calculated through Response Surface Analysis using Electronic Length Frequencies Analysis in the Fish Stock Assessment Tools program. Meanwhile, the spawning potential ratio (SPR) was analyzed based on data uploaded to the Barefoot Ecologist's Toolbox. The results showed that the asymptotic length (L?) at Atu Suasah and Lawe Melang Rivers was 750 mm and 759 mm, respectively, with K coefficients of 1.40 year-1 and 1.55 year-1. The length at first maturity (Lm50) of mahseer in these rivers was 372.52 mm and 438.88 mm. Total mortality (Z) is 3.88 year-1 and 3.24 year-1, while natural mortality (M) values are 1.06 year-1 and 0.91 year-1, with corresponding fishing mortality (F) rates of 2.82 year-1 and 2.33 year-1. The Beverton and Holt analyzes of per recruitment results showed that mahseer in Lawe Melang and Atu Suasah River have exceeded Emax, where the current E values ??were 0.73 year-1 and 0.72 year-1 respectively. These implied that mahseer stock was overfished with SPR 9% and 16% respectively, falling below the standard biological reference point. To ensure sustainability, conservation efforts should be put in place, including establishing a capture size limit and reducing fishing gear by 42%.